Estimation of Capsaicin Content of Two Varieties of Green Chilies by TLC Method - S Bhuvaneshwari, Dr (International Journal of Pharmaceutical & Biological Archive, 2014)
Estimation of Capsaicin Content of Two Varieties of Green Chilies by TLC Method